PROGRAM PRODUCER'S STRATEGY "HOW COULD IT GO VIRAL" IN ATTRACTING THE INTEREST OF VIEWERS ON NUSANTARA TV - Saskia, Fadila (Triwikrama: Jurnal Ilmu Sosial, 2025)
AbstractEach television station presents programs that it produces with various types of programs to attract the interest of a wide audience, including Nusantara TV. This research aims to determine the strategy of the "How Can It Go Viral" program in attracting audience interest using a descriptive qualitative approach and program strategy theory put forward by Morissan (2008). Data was obtained through interviews and documentation. In this research there are key informants and supporting informants as well as triangulation of sources as a test of data validity. The results obtained in this research refer to Morissan's theory, which has four aspects of strategic management of broadcast programs. First, the program planning carried out by the "How Can It Go Viral" Program on Nusantara TV is to use a comprehensive approach in its efforts to attract the attention of the audience. Then secondly, producing and purchasing programs is by selecting up-to-date content plus making direct productions using videos from YouTube. Followed by the third, namely program execution, in this case the "How Can It Go Viral" program involves and evaluates audience preferences, fourth is monitoring and evaluating the program, the "How Can It Go Viral" program continues to monitor and evaluate ongoing programs. This is done to keep the program relevant and interesting for the audience, who are expected to be able to adapt to the needs and changes that occur in the broadcasting industryKeywords: Digital Television, Program Strategy, Nusantara TV.